2021
DOI: 10.5603/cj.a2020.0135
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest treated by emergency medical service teams during COVID-19 pandemic: A retrospective cohort study

Abstract: Background: Out-of-hospital cardiac arrest (OHCA) is a challenge for medical personnel, especially in the current COVID-19 pandemic, where medical personnel should perform resuscitation wearing full personal protective equipment. This study aims were to assess the characteristics and outcomes of adults who suffered an out-of-hospital cardiac arrest in the COVID-19 pandemic treated by emergency medical service (EMS) teams. Methods: All EMS-attended OHCA adults over than 18 years in the Polish EMS registry were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
1
25
1
2
Order By: Relevance
“…Furthermore, preliminary data from the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic also presented a potential relationship with increased OHCA occurrence [29]. Borkowska et al [30] presented results regarding OHCA during the coronavirus disease 2019 (COVID-19) pandemic and reported that during March and April 2020 the OHCA incidence within Masovia Voivodeship was 12.2 per 100,000 inhabitants, which is lower in comparison to previous Polish studies [2][3][4]. However, it should be noticed that in March and April 2020 in Poland the epidemic was just starting to develop, the number of confirmed SARS-CoV-2 infections was very low and the first government restrictions were being implemented.…”
Section: The Highest Number Of Ohca Cases Was Observed On Monday and The Lowest Onmentioning
confidence: 99%
“…Furthermore, preliminary data from the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic also presented a potential relationship with increased OHCA occurrence [29]. Borkowska et al [30] presented results regarding OHCA during the coronavirus disease 2019 (COVID-19) pandemic and reported that during March and April 2020 the OHCA incidence within Masovia Voivodeship was 12.2 per 100,000 inhabitants, which is lower in comparison to previous Polish studies [2][3][4]. However, it should be noticed that in March and April 2020 in Poland the epidemic was just starting to develop, the number of confirmed SARS-CoV-2 infections was very low and the first government restrictions were being implemented.…”
Section: The Highest Number Of Ohca Cases Was Observed On Monday and The Lowest Onmentioning
confidence: 99%
“…Subsequently, this limits the number of ambulances available at a time, and to conduct resuscitation in protective suits, which, as many studies show, reduce the effectiveness of medical procedures, including chest compression. 2 , 3 , 4 …”
mentioning
confidence: 99%
“…To the best of our knowledge, this was the first meta-analysis focused on OHCA in the pandemic period comparing COVID-19 suspected or diagnosed patients to non-COVID-19 patients. Previous studies analyzed the first months of the pandemic with the corresponding periods in the years preceding the pandemic [ 38 , 39 , 40 , 41 ], making them more prone to bias. In contrast, this meta-analysis was based on the analysis of the incidence of OHCA during the COVID-19 pandemic, increasing the reliability of the results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%